Biblioeducation Media Based on Maldjustment Identification Self Counseling in SMPN 13 Padang - Aini, Syarifah (Lembaga Riset Mutiara Akbar, 2022)
This research was motivated by the presence of students who did maladjustment in the daily lives of students at school which was revealed by the BK teacher and strengthened by a virtual expression tool in the form of a questionnaire. In this study using research with the type of R&D (Development, where the population in this study was 889 students at SMP Negeri 13 Padang. The sample in the study was 92 students, namely class VII7, VIII2, and IX3, using the purposive sampling technique. is the right technique used in this study. The instrument used in this study is a questionnaire and to be analyzed with the percentage technique. This research will produce an educational biblio media based on the identification of virtual maladjustment self counseling in adolescents at SMP Negeri 13 Padang which is seen based on the identification results maladjustment is on the Many criteria and the educational biblio media is made based on the results of the maladjustment identification given in the form of media that has gone through a validity test with very acceptable criteria. Therefore, students can use the educational biblio media that has been made to reduce and prevent bullying. there is a maladjustment.